Beta-carotene supplementation attenuates cardiac remodeling induced by one-month tobacco-smoke exposure in rats - Zornoff, Leonardo Antonio Mamede [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP]; Dal Pai-Silva, M.; Carvalho, R. F.; Cicogna, Antonio Carlos [UNESP]; Padovani, Carlos Roberto [UNESP]; Novelli, E. L.; Novo, R.; Campana, A. O.; et al. (Oxford University Press, 2006)
Objective: the objectives were to analyze the cardiac effects of exposure to tobacco smoke (ETS), for a period of 30 days, alone and in combination with beta-carotene supplementation (BC). Research methods and procedures: Rats were allocated into: Air (control, n = 13); Air + BC (n = 11); ETS (n = 11); and BC + ETS (n = 9). In Air + BC and BC + ETS, 500 mg of BC were added to the diet. After three months of randomization, cardiac structure and function were assessed by echocardiogram. After that, animals were euthanized and morphological data were analyzed post-morten. One-way and two-way ANOVA were used to assess the effects of ETS, BC and the interaction between ETS and BC on the variables. Results: ETS presented smaller cardiac output (0.087 +/- 0.001 vs. 0.105 +/- 0.004 l/min; p = 0.007), higher left ventricular diastolic diameter (19.6 +/- 0.5 vs. 18.0 +/- 0.5 mm/kg; p = 0.024), higher left ventricular (2.02 +/- 0.05 vs. 1.70 +/- 0.03 g/kg; p < 0.001) and atrium (0.24 +/- 0.01 vs. 0.19 +/- 0.01 g/kg; p = 0.003) weight, adjusted to body weight of animals, and higher values of hepatic lipid hydroperoxide (5.32 +/- 0.1 vs. 4.84 +/- 0.1 nmol/g tissue; p = 0.031) than Air. However, considering those variables, there were no differences between Air and BC + ETS (0.099 +/- 0.004 l/min; 19.0 +/- 0.5 mm/kg; 1.83 +/- 0.04 g/kg; 0.19 +/- 0.01 g/kg; 4.88 +/- 0.1 nmol/g tissue, respectively; p > 0.05). Ultrastructural alterations were found in ETS: disorganization or loss of myofilaments, plasmatic membrane infolding, sarcoplasm reticulum dilatation, polymorphic mitochondria with swelling and decreased cristae. In BC + ETS, most fibers showed normal morphological aspects. Conclusion: One-month tobacco-smoke exposure induces functional and morphological cardiac alterations and BC supplementation attenuates this ventricular remodeling process.
Keywords: beta-carotene; smoking; cardiac function; hypertrophy; ventricular dilation